2020
DOI: 10.1002/jrs.5875
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive simultaneous monitoring of pH and depth using surface‐enhanced deep Raman spectroscopy

Abstract: Here we demonstrate the simultaneous recovery of multiplexed physical information of surface‐enhanced Raman scattering (SERS) nanoparticles (pH and depth) using deep Raman spectroscopy. As has been shown previously and in accordance with theory, inelastically scattered photons arising from spectral peaks that are suitably separated can exhibit different optical properties in the media through which they travel. These differences can impact the relative intensities of the Raman peaks as a function of the transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…9,10,1214,18,20,21 The frequency of the ν 8a ring breathing mode (around 1580 cm –1 ) is also known to shift with changing pH. 18,19,22 Other peaks are affiliated with the protonated or deprotonated state of the molecule, but have much lower intensity relative to the spectral features described. Indeed other molecules have pH-sensitive properties, but the MBA molecule is prominently used in the SERS literature, and thus the focus of the current study.…”
Section: Introductionmentioning
confidence: 94%
“…9,10,1214,18,20,21 The frequency of the ν 8a ring breathing mode (around 1580 cm –1 ) is also known to shift with changing pH. 18,19,22 Other peaks are affiliated with the protonated or deprotonated state of the molecule, but have much lower intensity relative to the spectral features described. Indeed other molecules have pH-sensitive properties, but the MBA molecule is prominently used in the SERS literature, and thus the focus of the current study.…”
Section: Introductionmentioning
confidence: 94%
“…[12][13][14] Over time the sophistication of signal retrieval has increased from identifying a single compound, 5,15 to multiplexed signal recovery, 13 physical property signal recovery 16 and depth localisation. [17][18][19][20][21] A number of publications have demonstrated how differential optical properties in a scattering medium, i.e. tissue, between different Raman components can also be exploited for depth localisation.…”
Section: Introductionmentioning
confidence: 99%
“…These examples have been demonstrated in well-controlled samples, wherein the sample has typically a uniform thickness in transmission geometry. [19][20][21] However, in the real world there is often little control of the sample thickness, when performing deep Raman on biological samples. This variation can arise undesirably in two key ways, firstly with thickness variation within a sample during Raman mapping, secondly due to differences in thickness between different samples.…”
Section: Introductionmentioning
confidence: 99%
“…87 More recently, a similar approach showed that it was possible to also precisely predict the depth at which SERS NPs were buried in a turbid phantom (0.5% intralipid) and simultaneously monitor changes in pH of the media surrounding the NPs. 88 need to establish more rapid, effective methods capable of quantifying neurotransmitter concentrations in vivo. With this in mind, SESORS has since been utilized for the measurement of melatonin, serotonin and epinephrine at concentrations as low as 100 mM in a brain tissue mimic through a cat skull.…”
Section: Assessment Of Bone Diseasesmentioning
confidence: 99%